The impact of Vitamin D deficiency on asthma, allergic rhinitis and wheezing in children: An emerging public health problem - Abdulbari Bener; Mohammad S Ehlayel; Hale Z Bener; Qutayba Hamid (Journal of Family and Community Medicine, 2014)
Background: Vitamin D deficiency has been declared a public health problem for both adults and children worldwide. Asthma and related allergic diseases are the leading causes of morbidity in children. The objective of this study was to investigate the potential role of Vitamin D deficiency in childhood asthma and other allergic diseases such as allergic rhinitis and wheezing. Materials and Methods: This cross-sectional study was conducted in Primary Health Care Centers (PHCs), from March 2012 to October 2013. A total of 2350 Qatari children below the age of 16 were selected from PHCs, and 1833 agreed to participate in this study giving a response rate of (78%). Face-to-face interviews with parents of all the children were based on a questionnaire that included variables such as socio-demographic information, assessment of nondietary covariates, Vitamin D intake, type of feeding, and laboratory investigations. Their health status was assessed by serum Vitamin D (25-hydoxyvitamin D), family history and body mass index. Results: Most of the children who had asthma (38.5%), allergic rhinitis (34.8%) and wheezing (35.7%) were below 5 years. Consanguinity was significantly higher in parents of children with allergic rhinitis (48.6%), followed by those with asthma (46.4%) and wheezing (40.8%) than in healthy children (35.9%) (P < 0.001). The proportion of severe Vitamin D deficiency was significantly higher in children with wheezing (23.4%), allergic rhinitis (18.5%), and asthma (17%) than in healthy children (10.5%). Exposure to the sun was significantly less in Vitamin D deficient children with asthma (60.3%), allergic rhinitis (62.5%) and wheezing (64.4%) than in controls (47.1%) (P = 0.008). It was found that Vitamin D deficiency was a significant correlate for asthma (odds ratio [OR] =2.31; P < 0.001), allergic rhinitis (OR = 1.59; P < 0.001) and wheezing (relative risk = 1.29; P = 0.05). Conclusion: The study findings revealed a high prevalence of Vitamin D deficiency in children with asthma and allergic diseases. Vitamin D deficiency was a strong correlate for asthma, allergic rhinitis and wheezing.